Sex differences among treatment clients with cocaine-related problems. (2nd January 2016) - Imtiaz, Sameer; Wells, Samantha; Macdonald, Scott
Abstract: Background : In a sample of treatment clients with cocaine-related problems, the present study examined sex differences in measures across six key domains, including socio-demographics, mental health, substance use, physical health, sexual health and psychosocial health. Methods : Data were utilized from a cross-sectional study of treatment clients in Ontario and British Columbia, Canada ( N = 417). t -Tests were used to examine sex differences in continuous measures, while Fisher's exact tests were used for dichotomous measures. A Bonferroni correction was applied to adjust for multiple comparisons. For measures that were significant in these tests, multivariable analyses were also conducted. Results : Females were found to be more likely than males to have lower personal and household incomes, report membership in sexual minority groups and engage in high risk sexual behaviors, including trading sex for money, trading sex for drugs and having sex when they did not want to. Males were more likely than females to report higher sexual compulsion scores and have paid for sex. Conclusion : Overall, the health-related needs of treatment clients with cocaine-related problems appear to differ by sex, especially in relation to sexual health. As such, setting of treatment priorities by treatment providers should reflect these important differences.